Anatomy of the vertebral vein - Slobodan Malobabić (Биомедицинска истраживања, 2024)
After a brief introduction about current anatomical terminology of the vertebral vein, different aspects of vertebral vein anatomy are considered, from basic anatomy, through the details about its specific parts (transverse and inferior parts) of the vertebral vein, to the ultrasonography data and their relationships to cerebral venous outflow. For transverse part controversial viewpoints are present regarding the position of the vertebral vein in relation to vertebral artery, the existence of one or more veins or of the venous plexus, including the findings that in this part, instead the venous vessels, there is a periosteal or dural sinus, like the cranial cavernous sinus. Also, the literature data about morphology and variations of inferior part (outside of transverse canal) of vertebral vein are reported. Only inferior part of vertebral vein is appropriately named, because of contradictory and different findings about its parts in transverse foramina and on atlas. Useful but not always the same imaging and ultrasonographic data about diameter, cross sectional area and blood flow in vertebral vein are Reviewsed. The clinical significance of the vertebral vein related to catheter insertions, and to different surgical procedures is mentioned, as well as some ultrasonographic findings of specific relationships of the vertebral vein and the cerebral outflow. Finally, in conclusions open issues about anatomy of the vertebral veins are listed and the problems requiring further study are indicated.
Keywords: vertebral vein; anatomy; transverse part; imferior part; ultrasonography.